Optimization of the training process with skilled athletes acrobatic rock and roll in the annual preparation of macrocycles based on model characteristics - N.P. Batieieva (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2014)
Purpose : to develop and prove experimentally the content of the special physical and technical training athletes. Material : the study involved 36 athletes (18 pairs). Results : to determine anthropometric indices athletes to perform matchmaking sports couple. Had the most significant biomechanical parameters of the exercise equipment. Developed a biomechanical model of the target technology implementation competitive exercise. Assessment methodology presented special physical and technical training. The technique of selection of partners based on a pair of sports: anthropometric and growth indicators weighty partner and partner. Conclusions : it was determined that the determining factor in successful sports couple acrobatic rock-roll the same rate of development of physical effort in joint actions. Characterized by quickness growth efforts, which develops on the joint angle straightening bio kinematic chain.